Ultrasonic vibration-assisted continuous wave laser surface drilling of materials. (April 2015) - Alavi, S. Habib; Harimkar, Sandip P.
Abstract: Melt expulsion and surface vaporization are important material removal mechanisms of pulsed laser drilling of materials. Drilling rate and quality of laser drilled holes depend on the material removal mechanism and are important considerations during laser drilling. In this letter, a novel ultrasonic vibration-assisted continuous wave laser drilling of materials is reported. The application of ultrasonic vibrations during laser surface melting facilitated melt expulsion from the surface, creating holes. Preliminary analysis of the material removal mechanisms and the effect of ultrasonic vibration amplitude on the geometric features are presented for the ultrasonic vibration assisted laser drilling of austenitic stainless steels.